Relationship Between Anthropometric Health Indexes with Food Consumption in Physically Active Elderly [Relación Entre Índices Antropométricos de Salud Con el Consumo de Alimentos en Adultos Mayores Físicamente Activos] - Herrera-Valenzuela, T (Grupo Aula Medica S.A., 2017)
Introduction: Programs focused on active aging do not always have actions to guide the elderly about healthy eating. Therefore, the concordance between the feeding habits and the morphological characteristics of this population group is little known. Objective: To correlate the anthropometric health indexes with the frequency of food consumption in physically active elderly (PAE). Methods: The sample consisted of 307 physically active Chilean elders of both sexes (8.4% males), with a mean age of 70.2 years. The studied variables corresponded to nutritional status, abdominal adiposity, cardiovascular risk and frequency of food consumption. A logistic regression model was applied, considering α< 0.05. Results: Fruit intake (OR = 0.12; 95% CI, 0.02-0.92) and water consumption (OR = 0.20; CI 95%, 0.04-0.90) are shown as protective factors for obesity; on the other hand, alcohol consumption (OR = 4.19; 95% CI, 1.03-17.02) and sweet snacks (OR = 10.68; 95% CI, 1.85-61.74) are presented as risk factors for obesity. In addition, vegetable intake (OR = 0.32; 95% CI, 0.11-0.92) was associated as a protective factor against abdominal adiposity and sweet snack consumption (OR = 6.45; 95% CI, 1.08-38.43) as a factor to present cardiovascular risk. Conclusion: The PAE that are more frequent in the consumption of healthy foods also show better nutritional status, abdominal adiposity and lower cardiovascular risk than active Chilean elderly who exhibit less healthy eating behaviors. © 2017, Grupo Aula Medica S.A. All rights reserved.